Is platelet monitoring during 7‐day lusutrombopag treatment necessary in chronic liver disease patients with thrombocytopenia undergoing planned invasive procedures? A phase IIIb open‐label study. Issue 10 (12th August 2020) - Numata, Kazushi; Tanaka, Katsuaki; Katsube, Takayuki; Ochiai, Toshimitsu; Fukuhara, Takahiro; Kano, Takeshi; Osaki, Yukio; Izumi, Namiki; Imawari, Michio
Abstract : Aim: Lusutrombopag is approved for thrombocytopenia in chronic liver disease patients planned to undergo invasive procedures. In previous clinical studies, lusutrombopag treatment was stopped in patients with an increase in platelet count (PC) of ≥20 × 10 9 /L from baseline and whose PC was ≥50 × 10 9 /L (discontinuation criteria). We assessed the influence of platelet monitoring during lusutrombopag treatment in lusutrombopag‐naïve patients. Methods: In this open‐label study, Child–Pugh class A and B (A/B) patients were enrolled and treated with lusutrombopag (3 mg/day) for 7 days. In the treatment‐naïve A/B‐1 group, the discontinuation criteria were applied on day 6. In the treatment‐naïve A/B‐2 group, the criteria were not applied. In a non‐naïve A/B group, the criteria were applied on days 3 and 5–7. The main efficacy end‐point was the proportion of patients without platelet transfusion (PT) before the primary invasive procedure. Results: In the A/B‐1, A/B‐2, and non‐naïve A/B groups, the proportions of patients without PT were 80.9% (38/47), 83.0% (39/47), and 75.0% (6/8), respectively. The mean durations of PC ≥ 50 × 10 9 /L without PT were 20.7, 20.3, and 22.8 days, respectively. Excessive PC increases (≥200 × 10 9 /L) were not detected in any group. Treatment‐related adverse events occurred in 4.3%, 6.4%, and 0% of A/B‐1, A/B‐2, and non‐naïve A/B patients, respectively. Severe portal vein thrombosis occurred in one A/B‐2 patient (PC 75 × 10 9 /L at onset). Conclusions: No meaningful efficacy and safety differences were observed among the groups with or without discontinuation criteria and the non‐naïve group. These findings support lusutrombopag treatment without platelet monitoring and retreatment with lusutrombopag.